Aplikasi AHP dalam Menentukan Kandidat Gubernur DKI Jakarta 2012-2017 - Rosta, Jevi; Tannady, Hendy (ComTech: Computer, Mathematics and Engineering Applications, 2013)
July 11, 2012 was chosen as an appropriate day in constitution terms to hold the election of Jakarta?s regional head for the next five years. There are many assumptions and opinions from some people about who would be elected as the governor of Jakarta. A lot of criteria from the candidates of governor and vice governor can be the parameters to be the success key in becoming Jakarta?s number one man. This research is discussing about decision making methods from many options by using AHP (analytical hierarchy process) method. Tthe case model is the election of Jakarta?s governor. The research utilizes two comparative components namely Jakarta?s governor and candidate of vice governor, as well as five criteria such as issues about  flood, transportation, economic, public services and credibility. The result of this research is the candidate with number six that should be most chosen in the election.